1982
DOI: 10.1099/0022-1317-59-2-295
|View full text |Cite
|
Sign up to set email alerts
|

Location and Characterization of the Antigenic Portion of the FMDV Immunizing Protein

Abstract: SUMMARYPurified foot-and-mouth disease virus (FMDV) of type OIK was treated with several endopeptidases of differing specificity. The immunizing protein VPTh r was cleaved into two detectable fragments by all enzymes except for glutamic acid-specific Staphylococcus aureus V8 protease. The longest fragments were generated by mouse submaxillary gland protease and the shortest by trypsin treatment of the intact virion. Several fragments, including the peptides resulting from the cyanogen bromide (CNBr) cleavage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
164
1
2

Year Published

1985
1985
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(171 citation statements)
references
References 19 publications
4
164
1
2
Order By: Relevance
“…For this study we cloned into an adenovirus vector the gene which expresses the precursor polyprotein of the four capsid proteins (P1) of FMDV. This polyprotein was chosen as it has been shown to contain most of the continuous and discontinuous B cell epitopes involved in the induction of neutralizing antibodies to FMDV (Bittle et al, 1982 ;Strohmaier et al, 1982 ;Saiz et al, 1994 ;Abrams et al, 1995 ;Brown, 1995 ;Mateu, 1995), as well as T-cell epitopes recognized by cattle and swine (Collen, 1994 ;Rodriguez et al, 1994 ;van Lierop et al, 1995). The conformation of the expressed products of this gene cloned into baculovirus and vaccinia vectors has been shown to be antigenically similar to native capsid proteins (Saiz et al, 1994 ;Sanz-Parra et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For this study we cloned into an adenovirus vector the gene which expresses the precursor polyprotein of the four capsid proteins (P1) of FMDV. This polyprotein was chosen as it has been shown to contain most of the continuous and discontinuous B cell epitopes involved in the induction of neutralizing antibodies to FMDV (Bittle et al, 1982 ;Strohmaier et al, 1982 ;Saiz et al, 1994 ;Abrams et al, 1995 ;Brown, 1995 ;Mateu, 1995), as well as T-cell epitopes recognized by cattle and swine (Collen, 1994 ;Rodriguez et al, 1994 ;van Lierop et al, 1995). The conformation of the expressed products of this gene cloned into baculovirus and vaccinia vectors has been shown to be antigenically similar to native capsid proteins (Saiz et al, 1994 ;Sanz-Parra et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…bodies recognize FMDV GH loop (residues 136-150 of capsid protein VP1 [2]), which includes several overlapping linear epitopes [3] and is also termed antigenic site A. Site A includes highly conserved residues, such as an Arg-Gly-Asp (RGD) motif, and two leucines ( 144 Leu, 147 Leu), which are deeply involved in cell and antibody recognition events [4].…”
Section: Introductionmentioning
confidence: 99%
“…First, the FMDV structures determined by Stuart and colleagues (16)(17)(18)(19) revealed that, contrary to other picornaviruses, no canyon or pit was present on the smooth FMDV surface. Furthermore, the critical receptor recognition Arg-Gly-Asp domain was located on a highly mobile loop (the G-H loop of VP1), which was also a major antigenic site for the virus (20)(21)(22). Additional structural work by Fita and colleagues (23) further indicated that the ArgGly-Asp motif is not only part of the receptor recognition site but it also interacts directly with some anti-viral neutralizing antibodies.…”
mentioning
confidence: 98%